Implementasi Evidence Based Nursing Pada Pasien Hipertensi dan Rehumathoid Arthritis : Studi Kasus - Putra, Muhammad Azhari; Dewi, Ratna (Universitas Fort De Kock Bukittinggi, 2020)
Background: Problems that occur in elderly patients not only involve the patient itself but also involve the family as the closest person to the patient. One important aspect of family nursing is the family, because the family is the smallest unit in society which is the client or the recipient of nursing care. To achieve good treatment outcomes, implementation of evidence-based nursing is needed. The purpose of this study is to present the implementation of eviden-based nursing with mernimun juice to reduce high blood pressure and warm lemongrass therapy to reduce pain intensity in the joints, each applied for 1 week. Method: In implementation, complementary therapy is applied to hypertension patients, given cucumber juice. Results: can show significant results in the reduction of high blood pressure that is before given the intervention TD: 180 / 100mmhg after given the intervention obtained TD: 130/90 mmhg and decreased pain intensity in hypertension patients using warm lemongrass compresses for 1 week. Conclusion: : The application of complementary therapies showed improvement in patients suffering from rheumatism, therefore, the application of evidence-based nursing in providing nursing care is recommended.